Aplikasi Penyimpanan Bukti E-Kinerja Asn Berbasis Web di Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Bukittinggi - Ismaini, Putri Bulkis; Zakir, Supratman; Sesmiarni, Zulfani; Aprison, Wedra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study refers to the problems found after conducting initial observations at the Faculty of Tarbiyah and Teacher Training at IAIN Bukittinggi, namely, e-performance evidence is stored on google drive, which causes the vulnerability to loss of proof of performance data. Then the confidentiality of performance evidence does not exist, because Google Drive can be opened by anyone who has access rights. And lastly, there is often a change of the password by the user, resulting in other users being unable to access it. With these problems, the authors designed a web-based ASN e-performance evidence storage application at the Faculty of Tarbiyah and Teacher Training IAIN Bukittinggi. This research wasconducted using the type of research R&D (Research and Development) using the SDLC (System Development Life Cycle) namely the Pressman version of the waterfall which consists of communication, planning, modeling, construction, and deployment. After the completion of the application system design,a product test is carried out consisting of a validity test, practicality test, and effectiveness test. Theresults of the experiment conducted by the author of the validity test obtained an overall average value of 0.80 with a valid category. Then the practicality test obtained an overall average value of 0.89 which was declared practical in the very high category. And the last is the effectiveness test obtaining an overall average value of 0.97 which is declared effective in the high category.